Human immunodeficiency virus–infected liver transplant recipients with incidental hepatocellular carcinoma: A prospective multicenter nationwide cohort study. Issue 5 (May 2017) - Agüero, Fernando; Forner, Alejandro; Valdivieso, Andrés; Blanes, Marino; Barcena, Rafael; Manzardo, Christian; Rafecas, Antoni; Castells, Lluis; Abradelo, Manuel; Barrera‐Baena, Pilar; González‐Diéguez, Luisa; Salcedo, Magdalena; et al.
Abstract : There is a lack of data on incidental hepatocellular carcinoma (iHCC) in the setting of liver transplantation (LT) in human immunodeficiency virus (HIV)–infected patients. This study aims to describe the frequency, histopathological characteristics, and outcomes of HIV+ LT recipients with iHCC from a Spanish multicenter cohort in comparison with a matched cohort of LT patients without HIV infection. A total of 15 (6%) out of 271 patients with HIV infection who received LT in Spain from 2002 to 2012 and 38 (5%) out of the 811 HIV– counterparts presented iHCC in liver explants ( P = 0.58). Patients with iHCC constitute the present study population. All patients also had hepatitis C virus (HCV)–related cirrhosis. There were no significant differences in histopathological features of iHCC between the 2 groups. Most patients showed a small number and size of tumoral nodules, and few patients had satellite nodules, microvascular invasion, or poorly differentiated tumors. After a median follow‐up of 49 months, no patient developed hepatocellular carcinoma (HCC) recurrence after LT. HIV+ LT recipients tended to have lower survival than their HIV– counterparts at 1 (73% versus 92%), 3 (67% versus 84%), and 5 years (50% versus 80%; P = 0.06). There was also a trend to a higher frequency of HCV recurrence as a cause of death in the former (33% versus 10%; P = 0.097). In conclusion, among LT recipients for HCV‐related cirrhosis, the incidence and histopathological features of iHCC in HIV+ and HIV– patients were similar. However, post‐LT survival was lower in HIV+ patients probably because of a more aggressive HCV recurrence. Liver Transplantation 23 645–651 2017 AASLD .